SARANA DAN PRASARANA DI PERPUSTAKAAN INDRA TAKSU DESA PACUNG DALAM PENINGKATAN PELAYANAN BERMUTU : SARANA DAN PRASARANA DI PERPUSTAKAAN INDRA TAKSU DESA PACUNG - aryan, gede (ACARYA PUSTAKA, 2024)
This research aims to find out how the use and function of facilities and infrastructure at the Indra Taksu Library in Pacung Village as a means for the community to increase interest in reading and quality services. This research uses descriptive research with interviews, as well as collecting documents related to facilities and infrastructure. In overcoming the demands for the quality of education, there needs to be maximum effort from the management. The management activity is the management of library infrastructure in improving the quality of education. This is the reason the researchers carried out this research. The type of research used by the author in this research is qualitative research which produces descriptive data. The data collection technique in this research uses three techniques, namely data is collected using interview, observation and documentation techniques. The data that has been collected is then analyzed inductively in three stages, namely: data reduction, data presentation, and drawing conclusions. Key words: Library, Services, Facilities and Infrastructure